Childhood Mortality in Nepal: Further Analysis of Nepal Demographic and Health Survey, 2022 - Kanel, Pawan (Nepal Population Journal, 2026)
This paper identifies the determinants effecting childhood mortality in Nepal using Nepal Demographic Health Survey 2022 (child) database by executing adjusted and stepwise logistic regression analysis. At the National level, the model (N=5372) identifies that number of children under 5 years, children ever born (CEB), births in the past 5 years, respondents desire for more children and sex of the child as strong predictors of childhood mortality. These same variables are also significant predictors for almost all the provinces. In addition to these indicators, age at first cohabitation, home delivery, employment and partner’s education for Koshi; rural/urban residence, partner’s education and Hindu religion for Madhesh; age at first birth, Hindu religion and partner’s education for Bagmati; joint decision on contraception and mother’s education for Lumbini; and twin child and age at first birth for Sudur Paschim Province are strong determinants effecting childhood mortality across the provinces of Nepal. If SDG Goal 3 Target 3.2 is to be met, these indicators need to be addressed immediately.